Evaluasi Usability Sosial Media Profesional "LinkedIn" Menggunakan Metode Usability Testing - Devita Helga Safitri; Hanifah Muslimah Az-Zahra; Mochammad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
LinkedIn is the world's largest professional networking platform on the internet. In use, 3 LinkedIn users were found who reported their difficulties through Google Play Store reviews and more than 10 people responded. The review contains complaints about difficult-to-understand guide issues, unclear account restriction information and a lack of understanding of LinkedIn's features. Furthermore, to clarify whether LinkedIn has usability problems, an initial survey was conducted among 21 college students which resulted in that 47.6% of respondents said LinkedIn's social media appearance was in the medium category, 38.1% of respondents said LinkedIn's appearance was in the complex category. Then 52.4% of respondents needed guidance the first time they used LinkedIn. LinkedIn is considered more towards complex social media than other social media. Based on the experience of respondents, stated that they experienced confusion the first time they used LinkedIn. The confusion they experience such as confusion where to start, unclear instructions and not knowing the functions of each LinkedIn feature. Therefore, it is necessary to evaluate the usability of the LinkedIn website which is focused on the main function of LinkedIn's social media, namely in terms of building profiles and connections using the usability testing method. The method is applied with a qualitative approach through thematic analysis. The results of the usability testing evaluation found a total of 27 usability problems which were grouped into 5 sections of the LinkedIn website features. These features include verification, sub menu plus profile section, settings, front profile and network.